Job Satisfaction of the SAAOs Working in Coastal Area of Bangladesh: A Case Study of Patuakhali District (The Agriculturists, 2010)
The study assessed different motivating and hygiene factors and determined the level of job satisfaction of the Sub-Assistant Agricultural Officers (SAAOs) of the Department of Agricultural Extension (DAE). Among 172 SAAOs in Patuakhali district, 58 per cent (90) were selected randomly as sample of the study. The findings show that scope of self growth, achievements in job and chance of promotion or advancement were rated the most three important motivators for bringing job satisfaction of the SAAOs. At the same time, salary, job status and job facilities were also identified as the most three important hygiene factors. Majority (81.1%) of the SAAOs had moderate satisfaction in performing their job, while 8.9 per cent of them had poor satisfaction and only 10 per cent SAAOs had high level satisfaction to their job. Out of eight selected characteristics of the SAAOs, education and problem confrontation had negative significant relationship with job satisfaction, while job facilities and job authority of the SAAOs had a positive significant relationship with their job satisfaction.